2016
DOI: 10.1007/s40009-016-0435-3
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Performance of Medicinal Plants on Traditional Oilseed and Pulse Crop of Central Himalaya, India

Abstract: The present study was aimed to determine the allelopathic effect of aqueous extract of above ground (AG) and below ground (BG) part of four medicinal plants (MAPs) viz., Picrorhiza kurroa, Asperagus racemosus, Ocimum sanctum and Valeriana wallichii on germination and seedling growth of some traditional food and oilseed crops. The aqueous extract of AG and BG part of the studied MAPs at 2 % significantly reduced the germination, plumule and radicle growth of the selected pulse and oil seed crops in bioassays. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Therefore, greater attention has been focused on the study of the allelopathic effects of medicinal plants and its potential application for weed control. More recently, some medicinal plants have been reported to possess allelopathic activity such as Ocimum tenuiflorum (Islam and Kato-Noguchi, 2013), Acacia concinna (Boonmee and Kato-Noguchi, 2017), Aspergus racemosus, Picrobiza kurroa, Valeriana wallichii, Ocimum sanctum (Rawat et al, 2016), and Melia azedarach (Shinwari et al, 2017). Therefore, these results suggested that medicinal plants with inhibitory activity may contain allelopathic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, greater attention has been focused on the study of the allelopathic effects of medicinal plants and its potential application for weed control. More recently, some medicinal plants have been reported to possess allelopathic activity such as Ocimum tenuiflorum (Islam and Kato-Noguchi, 2013), Acacia concinna (Boonmee and Kato-Noguchi, 2017), Aspergus racemosus, Picrobiza kurroa, Valeriana wallichii, Ocimum sanctum (Rawat et al, 2016), and Melia azedarach (Shinwari et al, 2017). Therefore, these results suggested that medicinal plants with inhibitory activity may contain allelopathic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…They found out that rice husk extract at 2% concentration level completely inhibited germination of cowpea seeds. In addition, the inhibitory effects of Picrorhiza kurroa, Asperagus racemosus, Ocimum sanctum, Valeriana wallichii (Rawat et al, 2016) and Ocimum basilicum L. (Verma et al, 2012) on germination and seedling growth of seed crops are in line with NL on sesame seeds. The effect of NA on sesame germination is detrimental, which suggests allelopathy.…”
Section: Resultsmentioning
confidence: 86%
“…Nasrine et al (2011) discovered that aqueous extracts of two medicinal plants (Euphorbia guyoniana and Retama retam) inhibited the germination of two invasive weeds (Bromus tectorum and Melilotus indica) and a common wheat (Triticum aestivum). Rawat et al (2016) also found that aqueous extracts of different plant parts extracted from four medicinal plants (Asperagus racemosus, Picrorhiza kurroa, Valeriana wallichii and Ocimum sanctum) affected development and significantly reduced the seed germination of the pulse and oilseed crops. These results also indicated that the inhibitory activity of the medicinal plants was due to the occurrence of allelochemicals.…”
Section: Introductionmentioning
confidence: 94%